Pengaruh Enterprise Resource Planning, Kualitas Sistem Informasi Akuntansi, Kompetensi, dan Pengendalian Internal pada Kinerja Perusahaan - Az Zahra, Adelia Aura; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 34 No 5 (2024)DO - 10.24843/EJA.2024.v34.i05.p18, 2024)
The study's objective is to learn how PT PLN Indonesia Power Bali Power Generation Unit's ERP deployment, accounting information system quality, human resource proficiency, and internal control systems have influenced the firm's performence. There were 175 workers included in the sample. Purposive sampling was used to choose the sample size of 48 respondents. Multiple liner regression analysis was used to examine the data. A favorable and statistically significant correlation was established between ERP installation, accounting information system quality, human resource competency, and internal control system maturity and financial performance. The quality of accounting information systems, qualified competences, and an efficient internal control system will all contribute to optimizing and improving the company's performance when ERP with a good performance is implemented. Keywords: Enterprise Resource Planning; Human Resource Competence; Company Performance